Effects of raster angle on the mechanical properties of PLA and Al/PLA composite part produced by fused deposition modeling. (22nd May 2019) - Zhang, Xinzhou; Chen, Lan; Mulholland, Tom; Osswald, Tim A.
Abstract : This paper studies the mechanical properties of polylactic acid (PLA) and aluminum fiber–reinforced PLA composite (Al/PLA) specimens fabricated by fused deposition modeling (FDM) process. The effect of raster angle (0°, 90°, 45°, 0°/90°, and ± 45°) on dynamic mechanical thermal property and tensile property of FDM‐printed PLA and Al/PLA has been studied. The results show reduced tensile strength and Young's modulus in Al/PLA composite specimen in comparison with pure PLA specimen. However, the elongation‐at‐break increases, which is due to Al fiber with the higher elasticity and lower tensile strength than PLA. The addition of Al fibers improves the dynamic mechanical thermal property of pure PLA because of the good interaction of the PLA matrix with the surrounding Al fibers. Raster angle plays an important role in FDM process. All specimens printed with 0° raster angle show highest tensile strength and dynamic mechanical properties, while specimens printed with 90° raster angle have the lowest values. Fractured surfaces indicate that the failure of the specimen with 0° raster angle is due to breaking of individual layers, while for 90° raster angle, specimen fails under separation of the adjacent raster layers.